Proyecto de factibilidad para la producción y comercialización de sobres autofiltrantes de guayusa, para la ciudad de Loja - Quevedo Rivera, Jenny Marisol (2016)
This research aims to determine the feasibility of the Project for the Production and Marketing of envelopes Maintenance Free Guayusa for the city of Loja, which aims to introduce to the market an innovative product that provides medical benefits for human health. We proceed to the application of surveys to a sample of 397 families, which allows to know the tastes and preferences Guayusa consumption in the city of Loja. The methodology describes the steps involved in the preparation of this research, where the development of the problem is highlighted, the market study allowed to know when and where the product according to customer requirements, even projecting a 15'810.333,00 unmet Guayusa envelopes units for the first year of life. In technical study size, location of the production plant which was determined based on the weight matrix of qualitative aspects, indicating that the optimum place for the implementation of the production plant is Loja Industrial Park, with establishing a Constitution 9'450.000 installed capacity of Guayusa envelopes units a year. Within the organizational study a company with limited liability, same as it is registered with the Superintendency of companies under the name "Guayusa del Sur" Co. is formed. Ltda. Activities are organized through manuals for defining the functions in each of the positions. 5 In the financial study disclosed a total investment of $ 307.466,83 which constitutes 67,48% of equity and debt capital 32,52%, also the financial assessment indicates a net present value of $ 294.111,78 an internal rate of return of 40,60% higher than the opportunity cost of money at a rate of 11,83%, indicating the benefit cost 0,52 cents profit for every dollar invested, the investment will be recovered in the second year, 3 months and 7 days; the sensitivity analysis supports increased costs 11,69% and 7,71% in the revenue decline, indicating that the investment project is feasible. Moreover it is concluded that the production cost per unit was established which is UDS 0,34 while the retail price is intermediary UDS 0,051 estimated annual sales of $ 433.755,00 in the first year of life up to $ 510.300,00 in the last year throwing $ 140.871,02 profit in the first year and $ 174.738,56 in the last year. It is recommended to implement the project because it contains the necessary technical elements that ensure the feasibility.